Risk factors for executive dysfunction after subthalamic nucleus stimulation in Parkinson's disease - Daniels, Christine; Krack, Paul; Volkmann, Jens; Pinsker, Markus O.; Krause, Martin; Tronnier, Volker; Kloss, Manja; Schnitzler, Alfons; Wojtecki, Lars; Bötzel, Kai; Danek, Adrian; Hilker, Rüdiger; et al. (Movement disorders, 2010)
A slight decline in cognitive functions and especially in executive functioning after deep brain stimulation (DBS) of the nucleus subthalamicus (STN) in patients with Parkinson's disease (PD) has been described. This study evaluated baseline parameters that contribute to a deterioration of cognitive functioning after DBS. We analyzed data from the neuropsychological protocol in a randomized controlled study comparing DBS with best medical treatment (BMT). Change scores were calculated for the cognitive domains "global cognitive functioning," "memory," "working memory," "attention," and "executive function." These domain-specific change scores were correlated with previously defined preoperative parameters. Compared with the BMT group (63 patients), the STN-DBS group (60 patients) showed a significant decline only in the domain executive function 6 months after DBS, which was significantly correlated with age, levodopa-equivalence dosage (LED) and axial subscore of the UPDRS in the off-medication state at baseline. Multiple regression analysis showed that these three factors explained, however, only about 23% of the variance. Patients with higher age, higher baseline LED, and/or higher axial subscore of the UPDRS at baseline have an increased risk for worsening of executive function after STN-DBS. High scores of these factors might reflect an advanced stage of disease progression. As these baseline factors explained the variance of the change score executive function only to a minor proportion, other factors including the surgical procedure, the exact placement of the electrode or postsurgical management might be more relevant for a decline in executive functioning after STN-DBS.